The effect of lentil on cholesterol-induced changes of serum lipid cardiovascular indexes in rats - Ahmad, Mousa Numan (Progress in Nutrition, 2017)
Aim: We investigated effects of lentil on serum lipemia and cardiovascular indexes in cholesterolfedrats. Methods: Sixty male Sprague-Dawley rats were assigned into 2 groups fed diets with or without cholesterol. Diets contained casein, raw dehulled lentil, raw whole lentil, cooked dehulled lentil or cooked whole lentil and given to rats for 4 weeks. Serum total cholesterol (TC), low-density lipoprotein cholesterol (LDLC), high-density lipoprotein cholesterol (HDL-C) and triglycerides (TG) were quantified and other biological parameters were assessed. Atherogenic indexes including atherogenic index of plasma (AIP), cardiac risk ratio (CRR), atherogenic coefficient (AC), HDL-C/LDL-C and TC/TG were then calculated. Results: Cholesterol induced marked atherogenic lipemia indicated by increased LDL-C and decreased HDL-C/LDL-C. Lentil increased (p